Tractatus 5.63-5.641 - Sanfélix Vidarte, Vicente (Analysis. Journal of Philosophical Research, 2022)
This article is a continuation of the article published in the journal Teorema, which offered an analysis of the paragraphs of the Tractatus from 5.6 to 5.621. Since 5.63-5.641 integrate with 5.6-5.621 a unitary group of thoughts, which I have called for short 5. 6ff, the basic bibliography that I recommended to get an idea of the dissension that reigns in the interpretation of those is still valid to understand the dissension that reigns in the interpretation of these, for if there is no agreement on whether Wittgenstein intends to criticize or defend solipsism, what arguments he uses, what kind of solipsism he considers, nor whether the position he considers deserves the name of solipsism, questions that at least partially can be answered from the analysis of 5. 6-5.621 this is largely because there is also no agreement on what is the nature of the self of solipsism, of the thinking, representative, metaphysical or philosophical subject (nor whether all these designations are equivalent) nor of its relation to the soul or subject as conceived by psychology, which are the main themes of 5.63-5.641.